Testosterone and Cardiovascular Health: Physiology, Pharmacokinetics and Clinical Implications - Shanmuganathan, Gaithrri; Lyang, Nora; Gill, Sandeep; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2026)
Cardiovascular disease (CVD) is becoming increasingly prevalent in the United States, prompting an interest in biological and hormonal contributors to risk. Although testosterone has long been implicated in cardiovascular risk, the nature of this relationship is complex and is not fully understood. Furthermore, the use of testosterone replacement therapy has increased over the years, especially in male hypogonadism. Like endogenous testosterone, the influence of testosterone replacement therapy on CVD risk remains unclear as findings from multiple studies have been inconsistent. Some studies proposed that testosterone replacement therapy -induced erythrocytosis may contribute to an increased risk of CVD, however, this association remains unconfirmed. Building on this proposed mechanism, some studies have found certain testosterone replacement therapy formulations to have increased rates of erythrocytosis while other studies found similar effects across all formulations. In this review, we outline the physiology of endogenous testosterone, its role in cardiovascular health and the current evidence surrounding testosterone replacement therapy and its relationship with CVD. We will then review the different testosterone replacement therapy formulations and evaluate their potential influence on CVD risk.